2011
DOI: 10.1016/j.ydbio.2011.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Robo1 and Robo2 have distinct roles in pioneer longitudinal axon guidance

Abstract: Pioneer longitudinal axons grow long distances parallel to the floor plate and precisely maintain their positions using guidance molecules released from the floor plate. Two receptors, Robo1 and Robo2, are critical for longitudinal axon guidance by the Slit family of chemorepellents. Previous studies showed that Robo1−/−;2−/− double mutant mouse embryos have disruptions in both ventral and dorsal longitudinal tracts. However, the role of each Robo isoform remained unclear, because Robo 1 or 2 single mutants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Unexpectedly, we previously observed that βIII-tubulin + cell bodies are located within the ventral midline of the hindbrain in E10.5 Robo1 −/− ; 2 −/− mutants (Kim et al, 2011). …”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Unexpectedly, we previously observed that βIII-tubulin + cell bodies are located within the ventral midline of the hindbrain in E10.5 Robo1 −/− ; 2 −/− mutants (Kim et al, 2011). …”
Section: Resultsmentioning
confidence: 84%
“…Primary antibodies were applied in PBST for 2–3 days. Our previous characterization of the Robo1 and Robo2 antisera showed specific labeling by immunofluorescence that was lost in homozygous mutants (Kim et al, 2011). After washing in PBST overnight, secondary antibodies (Jackson Immuno Laboratories) were applied in PBST for 2–3 days, followed by overnight washes.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…As noted in Section 3.1, this gene encodes a guidance molecule that helps neurons migrate to their correct location (Park et al 2002, Gonda et al 2013). However, the same molecule also becomes important in a different context, guiding the developing growth cones of axons as they extend to find the correct connectivity partners (Kim et al 2011, Kolodkin & Tessier-Lavigne 2011. The successful wiring up of a human brain is an amazing feat, considering that it is estimated to comprise ∼80 billion neurons (FonsecaAzevedo & Herculano-Houzel 2012) and that many of the connections are made between neurons located in distant regions.…”
Section: Wiring the Brain: Neurite Outgrowth And Connectivitymentioning
confidence: 99%
“…Slit proteins affect the trajectories of tracts that course longitudinally through the forebrain or rhombencephalic/spinal cord regions and whose origin is outside these regions [19]. This is the case of the ascending dopaminergic projection from the substantia nigra/ventral tegmental area complex that innervates the forebrain.…”
Section: In Vivostudies In Mice: Ascending Dopaminergic Pathwaysmentioning
confidence: 99%